The contribution of injection drug use to hepatitis C virus transmission globally, regionally, and at country level: a modelling study - Trickey, Adam; Fraser, Hannah; Lim, Aaron G; Peacock, Amy; Colledge, Samantha; Walker, Josephine G; Leung, Janni; Grebely, Jason; Larney, Sarah; Martin, Natasha K; Hickman, Matthew; Degenhardt, Louisa; et al. (The lancet. Gastroenterology & hepatology, 2019)
WHO aims to eliminate the hepatitis C virus (HCV) as a public health threat by 2030. Injection drug use is an important risk factor for HCV transmission, but its contribution to country-level and global epidemics is unknown. We estimated the contribution of injection drug use to risk for HCV epidemics globally, regionally, and at country level. We developed a dynamic deterministic HCV transmission model to simulate country-level HCV epidemics among people who inject drugs and the general population. Each country's model was calibrated using country-specific data from UN datasets and systematic reviews on the prevalence of HCV and injection drug use. The population attributable fraction of HCV transmission associated with injection drug use was estimated-defined here as the percentage of HCV infections prevented if additional HCV transmission due to injection drug use was removed between 2018 and 2030. The model included 88 countries (85% of the global population). The model predicted 0·23% (95% credibility interval [CrI] 0·16-0·31) of the global population were injection drug users in 2017, and 8% (5-12) of prevalent HCV infections were among people who currently inject drugs. Globally, if the increased risk for HCV transmission among people who inject drugs was removed, an estimated 43% (95% CrI 25-67) of incident HCV infections would be prevented from 2018 to 2030, varying regionally. This population attributable fraction was higher in high-income countries (79%, 95% CrI 57-97) than in countries of low and middle income (38%, 24-64) and was associated with the percentage of a country's prevalent HCV infections that are among people who inject drugs. Unsafe injecting practices among people who inject drugs contribute substantially to incident HCV infections globally. Any intervention that can reduce HCV transmission among people who inject drugs will have a pronounced effect on country-level incidence of HCV. None.